Nutritional Support in Malnourished Children With Compromised Gastrointestinal Function: Utility of Peptide-Based Enteral Therapy - Selimoglu, Mukadder Ayse; Kansu, Aydan; Aydogdu, Sema; Sarioglu, Aysugul Alptekin; Erdogan, Simge; Dalgic, Buket; Yuce, Aysel; Cullu Cokugras, Fugen (Frontiers in Pediatrics, 2021)
This review focuses on nutritional support in malnourished children with compromised gastrointestinal function addressing the interplay between malnutrition and gastrointestinal dysfunction, and the specific role of peptide-based enteral therapy in pediatric malnutrition. Malnutrition is associated with impaired gut functions such as increased intestinal permeability, malabsorption and diarrhea, while pre-existing functional gastrointestinal disorders may also lead to malnutrition. Presence of compromised gastrointestinal function in malnourished children is critical given that alterations such as malabsorption and increased intestinal permeability directly interfere with efficacy of nutritional support and recovery from malnutrition. Appropriate nutritional intervention is the key step in the management of malnutrition, while alterations in gastrointestinal functions in malnourished children are likely even in those with mild degree malnutrition. Therefore, nutritional therapy in children with compromised gastrointestinal function is considered to involve gut-protective interventions that address the overlapping and interacting effects of diarrhea, enteropathy and malnutrition to improve child survival and developmental potential in the long-term. Peptide-based enteral formulas seem to have clinical applications in malnourished children with compromised gastrointestinal function, given their association with improved gastrointestinal tolerance and absorption, better nitrogen retention/ balance, reduced diarrhea and bacterial translocation, enhanced fat absorption and maintained/restored gut integrity as compared with free amino acid or whole-protein formulas.